Attitudes towards doping and related experience in Spanish national cycling teams according to different Olympic disciplines - Morente-Sanchez, J.; Mateo-March, M.; Zabala, M. (PLOS ONE, 2013)
Attitudes towards doping are considered an influence of doping intentions. The aims of the present study were 1) to discover and compare the attitudes towards doping among Spanish national team cyclists from different Olympic disciplines, as well as 2) to get some complementary information that could better explain the context. The sample was comprised of seventy-two cyclists: mean age 19.67±4.72 years; 70.8% males (n = 51); from the different Olympic disciplines of Mountain bike -MTB- (n = 18), Bicycle Moto Cross -BMX- (n = 12), Track -TRA- (n = 9) and Road -ROA- (n = 33). Descriptive design was carried out using a validated scale (PEAS). To complement this, a qualitative open-ended questionnaire was used. Overall mean score (17-102) was 36.12±9.39. For different groups, the data were: MTB: 30.28±6.92; BMX: 42.46±10.74; TRA: 43.22±12.00; ROA: 34.91±6.62, respectively. In relation to overall score, significant differences were observed between MTB and BMX (p = 0.002) and between MTB and TRA (p = 0.003). For the open-ended qualitative questionnaire, the most mentioned word associated with "doping" was "cheating" (48.83% of total sample), with "responsible agents of doping" the word "doctor" (52,77%), and with the "main reason for the initiation in doping" the words "sport achievement" (45.83%). The major proposed solution was "doing more doping controls" (43.05%). Moreover, 48.67% stated that there was "a different treatment between cycling and other sports". This study shows that Spanish national team cyclists from Olympic cycling disciplines, in general, are not tolerant in relation to doping. BMX and Track riders are a little more permissive towards the use of banned substances than MTB and Road. Results from the qualitative open-ended questionnaire showed interesting data in specific questions. These results empower the idea that, apart from maintaining doping controls and making them more efficient, anti-doping education programs are needed from the earliest ages.